2017
DOI: 10.2485/jhtb.26.261
|View full text |Cite
|
Sign up to set email alerts
|

Ligature-Induced Periodontitis Increased Insulin Resistance and Triglyceride Levels in Wistar Rats

Abstract: In the present study, experimental periodontitis was induced by ligature in Wistar rats that were not on highfat or high-carbohydrate diet. The metabolic and infl ammatory parameters in the serum were examined in order to assess the eff ect of periodontitis-induced infl ammation on metabolic syndrome in individual without the genetic and dietary risk factors. Ligature-induced experimental periodontitis increased monocyte chemoattractant protein-1 and triglyceride levels in the serum, as well as homeostasis mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, similarly to other infectious or chronic inflammatory diseases [59], periodontal diseases might alter concentration and composition of plasma lipids and lipoproteins [60], promoting atherosclerosis and NAFLD progression. In fact, studies on different experimental periodontitis rodent models suggest that this condition led to increases in TGs [61,62] and total cholesterol and to a decrease in HDL-cholesterol [62,63]. However, Ebersole et al [64] reported an increase in serum cholesterol, but no change in TGs in a non-human primate model of ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similarly to other infectious or chronic inflammatory diseases [59], periodontal diseases might alter concentration and composition of plasma lipids and lipoproteins [60], promoting atherosclerosis and NAFLD progression. In fact, studies on different experimental periodontitis rodent models suggest that this condition led to increases in TGs [61,62] and total cholesterol and to a decrease in HDL-cholesterol [62,63]. However, Ebersole et al [64] reported an increase in serum cholesterol, but no change in TGs in a non-human primate model of ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, stimulation of adipocytes with CRP and inflammatory cytokines led to enhanced differentiation of adipocytes and elevated production of maturation-promoting proteinases such as matrix metalloproteinases [34]. Furthermore, induced experimental periodontitis in rats resulted in elevated levels of the monocyte chemotactic factor (monocyte chemoattractant protein-1) in serum and lipids in the liver [35]. Therefore, considering these epidemiological, in vitro , and animal data, our results suggest that good toothbrushing practices are effective in preventing periodontitis and, consequently, in reducing the risk of developing obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The ligature-induced periodontitis model has been used frequently in relatively large animals, including rodents, to assess the host response and its effects on the tooth-supporting tissues (gingiva and bone) under well-controlled conditions. The use of a ligature-induced periodontitis model is reliable and reproducible over a period of 10 days in rodents [ 14 ]. The effect of metformin on a periodontal disease experimental model was previously confirmed by our group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%